Design, development and testing of a sodium submersible Annular Linear Induction Pump for application in sodium cooled fast reactor. (15th September 2020) - Nashine, B.K.; Sharma, Prashant; Venkatesan, N.; Krishna Kumar, S.; Chandramouli, S.; Rajendra Prasad, R.; Vijayakumar, G.; Selvaraj, P.
Highlights: Design and development of a high temperature sodium submersible Annular Linear Induction Pump. Manufacture of pump using high temperature withstand winding made up of Mineral Insulated Cable. Performance evaluation of the pump in a sodium loop and pool meeting actual operating conditions. Comparison of experimental characteristics with theoretical characteristics. Long term endurance test of pump and design validation. Abstract: A sodium submersible Annular Linear Induction Pump (ALIP) has been developed for sodium draining at temperatures of 200 °C from the main vessel of Indian fast reactors if situation warrants. This ALIP does not require any external cooling when submerged in sodium. Due to non-availability of sodium submersible pressure sensor, difficulty was felt in obtaining differential pressure vs flow characteristic of ALIP when it is submerged in sodium; hence ALIP performance evaluation was carried out in two phases. In phase-1, the developed ALIP was tested in a sodium loop at 200 °C for obtaining pump characteristics. In phase-2, ALIP was submerged in a sodium pool up to temperature of 550 °C and tested. The combination of tests in sodium submergence and non-submergence in the two phases gave full range of performance evaluation of the developed ALIP. Design, development and testing of a sodium submersible ALIP are enumerated in this paper.